PATEN TANPA INVENTOR DALAM SEJARAH HUKUM PATEN INDONESIA - Ardiansyah, Levri (Fakultas Hukum Universitas Islam Indonesia, 2023)
This article identifies and analyzes the 'Patents without inventor' fact in Indonesian patent law. Specifically, the article shows via example in the 1984-2001 patent documents sourced from WIPO Patentscope, DJKI and LIPI. Even though the Law of the Republik of Indonesia Number 13 of 2016 has not been adopted, there have been patent documents and found in the patent documents the facts where the name of inventors were not mentioned. This article further emphasizes about 'The right of the inventor to be mentioned' in patent document. Legal systems regularly process a great deal of complexity and inconsistency, and thus, the disclosure of the 'Paten Without Inventor' fact is expected to clarify the importance of the definition of institutional inventor, inventorship and ownership, especially in anticipating the possibility of intellectual intelligence is deemed inventors.